Potential of Fatty Acid-Modified Spent Tea Leaves as Adsorbent for Oil Adsorption - Ang, Shu Ying; Nasaruddin, Nur Farhana Najwa; Abdul Halim, Hairul Nazirah; Mahmad Rozi, Siti Khalijah; Mokhtar, Zulfakar; Tan, Lian See; Che Jusoh, Nurfatehah Wahyuny (Progress in Energy and Environment, 2022)
Treatment of oil pollution remains a challenge due to the growing urbanisation. Thus, there is an increasing number of global studies on exploiting simple and effective methods to remove oil from water. In the present work, spent tea leaves (STL) have been modified using oleic acid (OA) and free fatty acids from waste cooking oil (FFA-WCO). The aim was to enhance the hydrophobicity of the STL so that they can act as an oil adsorbent. The functional groups of the fatty acids within the modified STL were identified using the Fourier Transform Infrared (FTIR) Spectroscopy analysis, while the surface morphology of STL was characterised using a Scanning Electron Microscope (SEM). The performance of the synthesised adsorbents for oil adsorption was tested in batch adsorption experiments. The FTIR results revealed that free fatty acids have been successfully impregnated onto the surface of STL. SEM analyses showed that the surface of the fatty acid-modified STL has smoother surfaces compared to the rougher surface of unmodified STL. From the batch adsorption test, the highest adsorption capacity was observed using 1:10 ratio of STL to WCO, with 120 min of contact time, 1 g of adsorbent dosage, and under the temperature of 45 °C. The adsorption capacity of STL@FFA-WCO at the optimum condition was 1.800 ± 0.15 g/g. For the effect of modification agents, STL that were modified using oleic acid (STL@OA) showed greater adsorption capacity of 2.267 ± 0.21 g/g. These findings proved that the fatty acid-modified STL have the potential of becoming green adsorbents for oil removal.